1978
DOI: 10.1159/000181375
|View full text |Cite
|
Sign up to set email alerts
|

Osteoscintigraphic Changes in Kidney-Transplanted Patients

Abstract: Technetium-99m-polyphosphate bone scintigraphy was performed in 105 kidney-transplanted patients. The pathological scintigraphic changes were classified as either (1) generalized, symmetrical or (2) focal accumulations of the tracer in the bones. 40 of the patients had normal scintigrams. 18 patients had generalized symmetrical scintigraphic changes alone, while focal scintigraphic changes were found in 14 patients without generalized changes and 33 patients had generalized as well as focal changes. The severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

1981
1981
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…The present investigation indicates that pulsed high postoperative steroids are major risk factors in the development of necrosis of the femoral head following renal transplantation (Heerfordt et al 1978, Stem and Watts 1979, Moms et al 1982, Haajanen et al 1985.…”
Section: Discussionsupporting
confidence: 49%
“…The present investigation indicates that pulsed high postoperative steroids are major risk factors in the development of necrosis of the femoral head following renal transplantation (Heerfordt et al 1978, Stem and Watts 1979, Moms et al 1982, Haajanen et al 1985.…”
Section: Discussionsupporting
confidence: 49%
“…An early sign in the present investigation is a lucent subcortical area (the crescent sign) (Griffiths et al 1974), presenting as a fracture line in the immediate subchondral bone, parallel to the articular surface. Heerfordt et al (Heerfordt et al 1978) demonstrated generalized and/or focal scintigraphic changes in renal transplant patients, 15 femoral heads showing an increased uptake. In 12 of the cases radiographic osteonecrosis was evident at the time of scintigraphy, but in the remaining 3 cases the scintigraphic signs of osteonecrosis preceded the radiographic appearance by a few months.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few of these patients developed osteonecrosis later than 4 years after transplantation. Although some studies have shown a relationship between prednisone and the development of posttransplant osteonecrosis (Elmstedt 1982;Harrington et al 1971;Heerfordt et al 1978;Ibels et al 1978), no definite correlation between the cumulated dose of prednisone and the risk of developing osteonecrosis has been found in others (Bewick et a/. 1976;Farge et al 1985;Feletti et al 1984;Haajanen et al 1985;Lausten et al 1989;Stern &Watts 1979).…”
Section: Discussionmentioning
confidence: 99%
“…1976;Elmstedt 1981;Haajanen eta/. 1985; Harrington e t a / . Heerfordt et al 1978;Ibels et a/. 1978).…”
unclassified